Propuesta de Mejoramiento para el sistema de transporte masivo de pasajeros en la localidad de Barranquilla y Soledad (2020)
In this exploratory – descriptive research, a characterization of the integrated mass transport system of the special, industrial and port district of Barranquilla and its metropolitan area called The Transmetro is constructed, in order to analyze how users, use it, its operation including its frequency and travel time from its starting stations to its final route destination; suggesting alternatives to improve such processes. They also identify, characterize and describe the fundamental factors of the Transmetro service, among them; the frequencies in which passengers use it, the times they invest to reach their destination point. To meet the objectives, a survey structured at 1,933 Transmetro users at different stations in Barranquilla and Soledad was applied as a data collection tool; the information collected was processed using statistical methods.